1991
DOI: 10.1007/bf02921787
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different strains of the yeastYarrowia lipolytica for citric acid production from glucose hydrol

Abstract: Four commercial strains and two mutants of the yeast species Yarrowia lipolytica were screened using batch fermentation. Strain Y. lipolytica A-101-1.14 (induced with UV irradiation) was found to be the most suitable for citric acid production from glucose hydrol (39.9% glucose and 2.1% other sugars), a byproduct of glucose production from potato starch. The specific rate of total citric and isocitric acid production was 0.138 g/g.h, the yield on consumed glucose 0.93 g/g, and the productivity achieved was as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
50
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 14 publications
5
50
0
1
Order By: Relevance
“…2 and 3). To the best of our knowledge, the highest Y Cit/S value for glucose or similarly metabolized compounds was reported by Wojtatowicz et al [7], who found a Y Cit/S of 0.93 g/g in experiments with a strain of Y. lipolytica grown on hydrolyzed potato starch containing 15% glucose. In contrast, in most reports lower yields were obtained compared with the present study (e.g., 0.45-0.60 g/g) [6, 11, 12, 16-18, 23, 28, 29, 33, 47].…”
Section: D912mentioning
confidence: 70%
See 1 more Smart Citation
“…2 and 3). To the best of our knowledge, the highest Y Cit/S value for glucose or similarly metabolized compounds was reported by Wojtatowicz et al [7], who found a Y Cit/S of 0.93 g/g in experiments with a strain of Y. lipolytica grown on hydrolyzed potato starch containing 15% glucose. In contrast, in most reports lower yields were obtained compared with the present study (e.g., 0.45-0.60 g/g) [6, 11, 12, 16-18, 23, 28, 29, 33, 47].…”
Section: D912mentioning
confidence: 70%
“…However, during the last few years numerous Yarrowia (Candida) lipolytica strains (natural or mutant) have been shown to be capable of producing citric acid in significant quantities during cultivation on various hydrophilic or hydrophobic substrates and fermentation configurations [6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Due to the easier handling of yeast compared to mold culture and the potential of growing yeasts on various carbon substrates, citric acid production has became one of the most important biotechnological applications of Y. lipolytica yeast [20].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, citric acid is considered to be the major bioproduct of this engineered strain. Previous research has reported citric acid production at a yield of 0.93 g/g of glucose hydrol from this yeast [38]. Another study reported a mass yield of 0.90 g citric acid from each gram of glycerol containing waste [34].…”
Section: Lipid Productionmentioning
confidence: 99%
“…To carry out fermentation processes, in addition to very expensive food raw materials, such as glucose [4][5][6][7] and plant oils [8][9][10], much cheaper substrates which are waste products of various industries, such as glycerol-containing waste of the biodiesel industry [9][10][11][12][13][14][15][16][17], glucose-containing wood hydrolysates [18,19], olive mill waste-water [20], and inulin [21] are used. Ethanol, a water-soluble individual compound which ensures the formation of a pure product and facilitates the isolation process, is also of great importance [22,23].…”
Section: Introductionmentioning
confidence: 99%